Application of buck three-level converter in power supply for water-cooled magnet - Li Chenkun (Dianzi Jishu Yingyong, 2018)
As the voltage stress of switches and the ripple of output voltage can be reduced effectively,the application of buck three-level converter would optimize the circuit design in power supply for water-cooled magnet.The operation of buck three-level converter are analyzed as well as parameter design and control method, and the Matlab/Simulink models are structured mainly based on the two circuit schemes，which validate the theoretic analysis results that the new scheme reduce the output ripple more significantly.